Biodiversity Conservation Education: An evaluation of Effects on Students’ Knowledge, Perception and Attitudes - Heavenlin, M.; Christy, I.Kanitha; Gunasekaran, Dr.C.; Rajkumar, V.; Chinnaraj, P. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The unsustainable exploitation of biodiversity by humanity has lead many of the earth’s natural resources to the brink of collapse. In order to reverse this trend, conservation educationist should reduce biodiversity illiteracy among the society, especially younger generation. Students are the future generation of the world. To evaluate the knowledge and attitude of the school students in biodiversity, various analysis and awareness was carried out. In our contribution, we focused on finding the differences between primary school students’ attitudes towards biodiversity between their demographic variables such as gender, class level, family type, type of school and family income. The sample consists of 814 students from 10 schools. Students of grades 7th, 8th and 9th were analysed. Data were evaluated with factor analysis and SPSS. The study emphasizes on the necessity to impart education for students regarding biodiversity. According to the results of the analysis of students’ point of attitude towards biodiversity, in terms of variables; a significant differences were found in favour of students, female students, and students in joined family and parent’s education status.